“EFEKTIFITAS PERAN SDM POKTAN ROSAN JAYA DALAM PROSES KOMUNIKASI INTERPERSONAL UNTUK MEMBANGUN KOMITMEN, KINERJA, DAN TEAMWORK - Basuki, Ibrahim Qolby Jatio; Wihara, Dhiyan Septa (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
One of the important skills that must be possessed by HR in organizational life is interpersonal communication. In interpersonal communication, the relationship takes place face-to-face, so that feedback and responses from the interlocutor can be known. What is to be achieved in this study is to find out how important interpersonal communication is in building commitment, performance, and teamwork in farmer groups. As well as to determine the ability and willingness of the role of human resources in farmer groups to establish interpersonal communication in building commitment, performance, and teamwork.The research used is descriptive qualitative using case study method. Case study data can be obtained intensively from the parties concerned, and collected from various sources directly. The result is that understanding the meaning of interpersonal communication in building commitment, performance, and teamwork in Rosan Jaya farmer groups is very important. The ability of farmer groups and farmers to establish interpersonal communication so that each party can hold fast to the commitment, performance, and teamwork as a common goal has become a habit for a long time. The willingness of farmer groups and farmers to make sacrifices in order to maintain commitment, performance, and teamwork is quite good.